The Semantic Expansion and Sociolinguistic Functions of ‘‘Yapping’’ in Gen Z Tiktok Discourse - Bulu, Stefania; Erfiani, Ni Made Diana; Awololon, Yohanes Octovianus Lesu (Kajian Linguistik dan Sastra, 2026)
Digital communication on TikTok has accelerated the emergence and transformation of lexical expressions among Generation Z users. One of the popular terms in digital discourse is ‘Yapping’, which lexically refers to excessive talking. However, in its use on TikTok, the term has undergone semantic expansion and contextual meaning shifts influenced by social interaction and digital culture. This research aims to analyze the semantic functions of the term ‘Yapping’ and identify its sociolinguistic functions in Generation Z’s TikTok discourse. This research employed a descriptive qualitative approach using digital discourse analysis. The data consisted of TikTok videos, captions, and comments containing the term ‘Yapping’, collected through non-participant observation and digital documentation techniques. Data analysis involved identifying contexts of use, classifying semantic variations, and interpreting the social functions of the language. The findings reveal that the meaning of “Yapping” in TikTok discourse is highly contextual and extends beyond its original negative lexical meaning. The term is used to express humor, communication enthusiasm, emotional openness, interpersonal affection, and self-identity. In some contexts, “Yapping” acquires positive meanings related to confidence and social connection, while in others it still reflects excessive or emotionally exhausting speech. Sociolinguistically, the term functions as a marker of group identity, emotional expression, social validation, and interpersonal relationship negotiation among Generation Z users. Furthermore, the study reveals that the evolving use of ‘Yapping’ reflects the multimodal, interactive, and algorithm-driven characteristics of contemporary digital discourse on TikTok.  Abstrak Perkembangan media sosial, khususnya TikTok, melahirkan bentuk komunikasi digital yang dinamis dan memengaruhi perkembangan bahasa Generasi Z. Salah satu istilah yang populer dalam wacana digital adalah ‘Yapping’, yang secara leksikal berarti berbicara secara berlebihan. Namun, dalam praktik penggunaannya di TikTok, istilah ini mengalami perubahan dan perluasan makna yang dipengaruhi oleh konteks sosial serta budaya digital. Penelitian ini bertujuan untuk menganalisis fungsi semantik istilah ‘Yapping’ serta mengidentifikasi fungsi sosiolinguistik penggunaannya dalam wacana digital Generasi Z di TikTok. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis wacana digital. Data berupa video, caption, dan komentar TikTok yang mengandung istilah ‘Yapping’ dikumpulkan melalui observasi non-partisipan dan dokumentasi digital. Analisis dilakukan melalui identifikasi konteks penggunaan, klasifikasi makna, serta interpretasi fungsi sosial bahasa. Hasil  penelitian menunjukkan bahwa makna istilah “Yapping” dalam wacana TikTok bersifat sangat kontekstual dan tidak lagi terbatas pada makna leksikal negatifnya. Istilah ini digunakan untuk mengekspresikan humor, antusiasme berkomunikasi, keterbukaan emosional, afeksi interpersonal, dan identitas diri. Dalam beberapa konteks, “Yapping” memperoleh makna positif yang berkaitan dengan kepercayaan diri dan hubungan sosial, sementara dalam konteks lain istilah ini masih merepresentasikan perilaku berbicara berlebihan atau melelahkan secara emosional. Secara sosiolinguistik, istilah ini berfungsi sebagai penanda identitas kelompok, ekspresi emosional, validasi sosial, dan negosiasi hubungan interpersonal di kalangan Generasi Z. Selain itu, penggunaan “Yapping” juga mencerminkan karakteristik wacana digital TikTok yang multimodal, interaktif, dan partisipatif.